2014
DOI: 10.4236/ajps.2014.513219
|View full text |Cite
|
Sign up to set email alerts
|

Red Rice Control and Soybean Tolerance to <i>S</i>-Metolachlor in Association with Glyphosate

Abstract: Red rice is one of the major troublesome and difficult weeds to control in rice production regions. The introduction of the Clearfield ® technology allowed producers to control red rice using rice genotypes tolerant to the imidazolinone herbicides. However, because the consecutive use of this technology red rice biotypes have evolved resistance to imidazolinone herbicides, the rice-soybean rotation has been an alternative used by producers to control this weed. This system allows the use of herbicides with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Similarly, the genotype and climatic conditions can influence the responses to the application of different herbicides and mixes for weed control. Research that has been carried out with other crops, such as sugar cane (Costa et al 2012), wheat (Galon et al 2015), rice (Pinto et al 2008) and soybean (Zemolin et al 2014), demonstrated different responses of genotype to the application of herbicides, with frequent problems of phytotoxicity and, sometimes, the loss of crop productivity or impairment of the quality of the final product. However, it is noted that, for corn, few studies have evaluated the influence of the main herbicides that are applied by producers, alone or in tank mix, on the agronomic characteristics of the cultivar.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the genotype and climatic conditions can influence the responses to the application of different herbicides and mixes for weed control. Research that has been carried out with other crops, such as sugar cane (Costa et al 2012), wheat (Galon et al 2015), rice (Pinto et al 2008) and soybean (Zemolin et al 2014), demonstrated different responses of genotype to the application of herbicides, with frequent problems of phytotoxicity and, sometimes, the loss of crop productivity or impairment of the quality of the final product. However, it is noted that, for corn, few studies have evaluated the influence of the main herbicides that are applied by producers, alone or in tank mix, on the agronomic characteristics of the cultivar.…”
mentioning
confidence: 99%
“…Control (%) of Alexander grass (Urochloa plantaginea) that was infesting the corn hybrid, SYN 7B28, due to the application of herbicides atErechim, Brazil, in 2013/2014 …”
mentioning
confidence: 99%
“…(1 decreased soybean height by 5 to 13%, whereas Zemolin et al (2014) reported as much as a 70% reduction in soybean height from S-metolachlor at 3000 g a.i. ha…”
Section: Soybean Heightmentioning
confidence: 99%
“…S-metolachlor, flumioxazin or saflufenacil applied PRE (Miller et al 2012;Mahoney et al 2014;Zemolin et al 2014). Friesen and Wall (1985) reported up to 20% soybean injury due to 400 g a.i.…”
Section: Crop Injurymentioning
confidence: 99%
“…Adopting sustainable and conservative production systems, in combination with alternative crops with commercial value and liquidity, such as soybeans, can contribute to the maintenance of productive competitiveness in the lowlands areas of this state (Vernetti Jr et al, 2009). Besides, this strategy can reduce the problems associated with the presence of weeds resistant to imidazolinone herbicides, such as weedy rice (Oryza sativa), providing more options for chemical control with different action mechanisms (Zemolin et al, 2014). Sulfentrazone, which belongs to the aryl triazolinone chemical group, can be used in the weed control as a pre-emergent herbicide for soybean (Senseman, 2007).…”
Section: Introductionmentioning
confidence: 99%